If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9w+5=(3w-1)
We move all terms to the left:
9w+5-((3w-1))=0
We calculate terms in parentheses: -((3w-1)), so:We get rid of parentheses
(3w-1)
We get rid of parentheses
3w-1
Back to the equation:
-(3w-1)
9w-3w+1+5=0
We add all the numbers together, and all the variables
6w+6=0
We move all terms containing w to the left, all other terms to the right
6w=-6
w=-6/6
w=-1
| 17.5=35/x | | 8h-7=-113 | | z/4+2=-77 | | 100x=(x=0.83333) | | y+y+y-10+3y=20 | | 82+0.6(h)=85 | | 6h+16=64 | | -17y+18=-16y | | -3+6-3x-1=-103 | | -3x+80+23=5x-17 | | 82+0.69(h)=85 | | h(3)=-16(3)^2+98(3)+7.5 | | 9x+6-3x-1=-103 | | (2x+9)+5x=180 | | 60x-50+30x-250=-8x-20+25x | | -w/5-2=8 | | (-3x+80)+23=5x-7 | | 2x-10-3x-4=-22 | | 0.75n-18=0.25(n-16) | | (9/4)(w-(1/9))=7/2 | | -5/v-5=-8 | | 20x-3=40x+9 | | 129-x=250 | | 19f+23-7f=187+-39 | | -2x-10-3x-4=-22 | | 24=w+2w | | -x/7=-54 | | 1.2=-32b | | -4+2/5x=18 | | 9f+3=22 | | 26=90n | | 2(3-2x)=4 |